THE INFLUENCE OF COUNTRY IMAGE, BRAND FAMILIARITY, PRODUCT QUALITY, AND SOCIAL INFLUENCE TOWARDS PURCHASE INTENTION : THE CASE STUDY OF SAMSUNG - Jacob, Michael Rusiviro; Tan, Pauline Henriette Pattyranie (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2021)
Abstract:  The smartphone industry has grown rapidly in recent years, and one of the market leaders is Samsung. Over the past few years, Samsung has been remaining as the top brand in the smartphone industry worldwide and has maintained its market share in the world. However, this is not the case in Indonesia. In recent years, Samsung in Indonesia has also experienced a dwindling market share, that is why it is interesting to conduct in-depth research on its consumer purchase intentions. Therefore, this study utilizes Country Image, Product Quality, Brand Familiarity as independent variables to explore their influence on Samsung smartphone purchase intentions to examine the nature of Samsung’s consumer purchase intentions and then to provide some recommendations on how Samsung can increase its market share in Indonesia. This study used primary data by using convenience sampling. The data analysis used Structural Equation Modeling (SEM) through SmartPLS and the results showed that Product Quality, Brand Familiarity, and Social Influence had a positive and significant effect on Purchase Intention, while the State Image proved insignificant. Abstrak: Industri smartphone telah berkembang pesat dalam beberapa tahun terakhir, dan salah satu pemimpin pasarnya adalah Samsung. Selama beberapa tahun terakhir, Samsung telah bertahan sebagai merek teratas dalam industri ponsel pintar di seluruh dunia dan telah mempertahankan pangsa pasarnya di dunia. Namun tidak demikian halnya di Indonesia. Dalam beberapa tahun terakhir, Samsung di Indonesia juga mengalami pangsa pasar yang semakin menipis, oleh karena itu menarik untuk dilakukan penelitian mendalam tentang niat beli konsumennya. Oleh karena itu, penelitian ini memanfaatkan Country Image, Kualitas Produk, Brand Familiarity sebagai variabel independen untuk mengeksplorasi pengaruhnya terhadap niat beli smartphone Samsung untuk mengetahui sifat niat beli konsumen Samsung dan kemudian memberikan beberapa rekomendasi bagaimana Samsung dapat meningkatkan pangsa pasarnya di Indonesia. Penelitian ini menggunakan data primer dengan menggunakan convenience sampling. Analisis data menggunakan Structural Equation Modeling (SEM) melalui SmartPLS dan hasil penelitian menunjukkan bahwa Kualitas Produk, Keakraban Merek, dan Pengaruh Sosial berpengaruh positif dan signifikan terhadap Niat Membeli, sedangkan Citra Negara terbukti tidak signifikan  Keywords:  International business, global marketing, consumer behaviour, purchase intention, country image, product quality, brand familiarity, social influence Kata Kunci:    Bisnis internasional, pemasaran global, perilaku konsumen, niat membeli, citra negara, kualitas produk, keakraban merek, pengaruh sosial